Avengers : beyond / Derek Landy, writer ; Frank D'Armata, colorist ; Cory Petit, letterer. - Landy, Derek (Marvel Comics, 2023)
Someone has been manipulating the Avengers for months, altering the very fabric of reality in an attempt to prepare the planet for a threat that could destroy everything. Now this all-powerful puppeteer is about to be dragged, kicking and screaming, into the light. Meanwhile, as violence tears New York apart, Janet Van Dyne fights not only to save the lives of her fellow heroes, but also a friendship! But time may have run out, for the Lost One has arrived - knocking on Earth's door, waiting to be let in. In a desperate attempt to keep that door shut, a depleted team of Avengers battles the Black Order in the veins and arteries of the dead Celestial they call home. Blood is spilled, bones are broken and betrayal is on the horizon - but who are the Bootleg Avengers?